The utility of serial echocardiograms for organ procurement in brain death. Issue 11 (15th October 2017) - Lazzeri, Chiara; Guetti, Cristiana; Migliaccio, Maria L.; Ciapetti, Marco; Peris, Adriano
Abstract: Heart transplantation rates are limited by a shortage of donor hearts, and left ventricular dysfunction is an important cause. We hypothesized that an early echocardiographic evaluation in severe brain injury (performed within 12 hours from ICU admission) could allow the detection of potentially reversible left ventricular (LV) abnormalities and thus the initiation of tailored treatment whose effects could be assessed at a second echocardiogram performed when brain death develops. We assessed this hypothesis in 49 patients with severe brain injury who were potential heart donors. A reduction in LV ejection fraction (LVEF) (<55%) was present in five patients (10.2%): diffuse hypokinesia in three patients (6.1%), segmental wall motion abnormalities in two (4.1%). Two patients showed apical ballooning (normal LVEF). The three patients with diffuse hypokinesia showed, at the echocardiogram performed 12 hours later, a complete recovery of wall motion and LVEF. Among patients with apical ballooning, a complete resolution was observed in both patients. Two patients were considered potentially eligible for heart donation, resulting in 20% increase in donor retrieval rate. In serious encephalic lesions, potentially evolving toward brain death, echocardiography performed after ICU admission allowed the identification of LV abnormalities, which could be specifically treated with complete resolution.